Complex system of developing information and communication competence - Chernysheva T. Yu. Tatiana Yurievna; Molnina E. V. Elena Vladimirovna; Telipenko E. V. Elena Viktorovna; Tomilov I. N. Ivan Nikolaevich; Min’kov S. L.; Zakharova A. A. Aleksandra Aleksandrovna (Information and communication technologies, 2016)
Title screen